POTENTIAL OF OXALIS CORNICULATA LINN IN THE TREATMENT OF ULCERATIVE COLITIS - SANTOSH B. DIGHE; B. S. KUCHEKAR; SAGAR B. WANKHEDE (International Journal of Pharma and Bio Sciences, 2015)
Oxalis corniculata Linn (Oxalidace) is an Indian medicinal plant which is widely used as food and folk medicine. Present work was aimed to check the potential of Oxalis corniculata Linn leaf extract in the treatment of ulcerative colitis. Dried and powdered leaves were extracted using petroleum ether, chloroform, ethyl acetate and methanol. The extracts at a dose of 100 mg/kg were screened for acetic acid induced ulcerative colitis in mice. The antioxidant potential of extracts was evaluated by DPPH method. It was observed that liver and kidney functions were not affected in mice after administration of ethyl acetate and methanol extract for fifteen days. Treatment with ethyl acetate extract of Oxalis corniculata Linn showed superior antiulcer, antioxidant activity and better protective effect compared to other extracts. Myeloperoxidas and malondialdehyde level in blood and tissue was decreased significantly after administration of ethyl acetate and methanol extracts in mice.